PENGARUH BELANJA MODAL, TENAGA KERJA DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DI KOTA LHOKSEUMAWE - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2020)
Capital expenditure is an expenditure that can be said as a routine expenditure in the framework of forming existing capital. In this case the capital expenditure in question could be land, equipment and machinery, buildings and buildings, networks, or in other physical forms, such as books, animals and so forth. manpower is anyone who is capable of doing work to produce goods or services either to meet their own needs or for the community. investment means the purchase (and production) of the capital of goods not consumed but used for future production. This study aims to determine the effect of capital expenditure, labor and investment on economic growth in the city of Lhokseumawe. This study uses secondary data for 10 years from 2006-2015. Data analysis method used in this research is (OLS). Data used in this research is time series from year 20062015. The results showed that the three variables of capital expenditure (X1) have positive and significant effect on economic growth (Y) in Lhoseumawe city, Labor (X2) have positive and significant effect to economic growth (Y) in Lhokseumawe city and investment has negative and insignificant effect on economic growth (Y) in the city of Lhokseumawe.